Chapter 8 Storylining Climes - Shepherd, Theodore G. (Taylor & Francis, 2023)
Modern climate science aims to explain and predict climate based on spatio-temporally invariant laws of nature. This physics-based mindset largely displaced a more contingent, historical approach to climate. However, what is being called the "storyline" approach to climate science has recently been gaining traction. Although storylines are well-established vehicles in many scholarly disciplines, their use in physical climate science is radical insofar as they immediately raise questions such as "Who tells the stories?" and "Whose stories get told?" Such a personalization of climate science aligns with the concept of clime. This chapter reflects on various traditions in the hitherto remotely related disciplines of climate science and anthropology, and experiments with integrating different forms of knowledge in the sweetgrass-braiding fashion. Drawing on two illustrations of natural disasters, in Nepal and Alaska, four potential threads for a productive dialogue between climate science and the environmental humanities are identified: (i) time; (ii) agency and intentionality; (iii) chaos, both temporal and spatial; and (iv) dichotomies in ways of knowing, most notably between descriptive and explanatory traditions. Through the device of contingency and by enlivening ethnography, it becomes possible to storyline climes.